Production and growth curve of pickling cucumber plants in conventional and alternative pest control (Revista de Ciências Agroveterinárias, 2013)
Aiming to evaluate the production and the dynamics of productive increment of pickling cucumber plants, an experiment was carried out at the Epagri, Ituporanga Experimental Station, Santa Catarina State, Brazil, from January to March 2011. The test was conducted in splitplots in time in in a randomized block design, with four replications. The factors used were two production systems (conventional and differentiated) in the plots and three cultivars of cucumber (Marinda, Premium and Zapata) in the subplots. The plots were composed of four lines of 3 m in length, spaced 1.0 x 0.30 m apart with one plant per hill and the floor area consisting of central lines. We evaluated the production of fresh fruit per plant (g plant-1), productivity (t ha-1), fruit weight (g), number of fruits per plant, percentage of commercial fruit and percentage of infested fruit. For the accumulated data on the number of fruits per plant and yield of fresh fruit, depending on harvest days, we adjusted the logistic model to determine the maximum accumulated for each variable. The production of fresh fruit per plant and productivity were not affected by cropping systems, whose values were 538.9 g and 17.9 t ha-1, respectively. The loss per infested fruit was higher in the differentiated system, but was still with high percentage of commercial fruit, from 78.6 to 87.2%. The industry should evaluate whether the sale of a healthier product can attract more consumers and offset the losses observed.
Keywords: Production system; Cucumis sativus; Diaphania spp.